Enhancing the Phytoremediation of Hydrocarbon-Contaminated Soils in the Sudd Wetlands, South Sudan, Using Organic Manure - J. A. Ruley; A. Amoding; J. B. Tumuhairwe; T. A. Basamba; E. Opolot; H. Oryem-Origa (Applied and Environmental Soil Science)
Phytoremediation of hydrocarbon-contaminated soils is a challenging process. In an effort to enhance phytoremediation, soil was artificially contaminated with known concentration of light crude oil containing Total petroleum hydrocarbon (TPH) at a concentration of 75 gkg−1 soil. The contaminated soil was subjected to phytoremediation trial using four plant species (Oryza longistaminata, Sorghum arundinaceum, Tithonia diversifolia, and Hyparrhenia rufa) plus no plant used as control for natural attenuation. These phytoremediators were amended with concentrations (0, 5 and 10 gkg−1 soil) of organic manure (cow dung). Results at 120 days after planting, showed that application of manure at concentrations of 5 and 10 gkg−1 soil combined with an efficient phytoremediator can significantly enhance reduction of TPH compared to natural attenuation or use of either manure or a phytoremediator alone (p<0.05). The study also showed that a treatment combination of manure 5 gkg−1 soil, with a phytoremediator gives a similar mean percentage reduction of TPH as manure 10 gkg−1 soil (p>0.05). Therefore, the study concludes that use of phytoremediators and manure 5 gkg−1 soil could promote the restoration of TPH contaminated-soils in the Sudd region of South Sudan.